1986
DOI: 10.1210/endo-119-3-1048
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Specific Estradiol Binding Site on Rat Pituitary Membranes

Abstract: Using adenohypophyses from normal female rats, we demonstrate that estradiol binds pituitary membranes to one homogeneous population of sites with high affinity [dissociation constant (Kd) = 0.041 +/- 0.014 nM; n = 6] and low capacity [maximum binding (Bmax) = 13.6 +/- 5.6 fmol/mg protein]. The binding is thermolabile. Association experiments show that the best experimental conditions are an overnight incubation at 0 C. When the amount of proteins is increased more than 0.3 mg/ml of membrane suspension, bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 22 publications
2
28
1
Order By: Relevance
“…A second messenger pathway is possible if the hormone receptors are associated with membranes or alternatively if the hormone is able to affect directly the membrane-associated signal-transducing enzymes during its passage through the membrane. The presence of specific binding sites for steroid hormones on the membrane of endometrial cells (Pietras & Szego 1977), rat pituitary (Bression et al 1986, Pappas et al 1995 has been demonstrated. Furthermore, Grove & Korach (1987) and Freter et al (1988) have shown enhanced phosphatidyl inositol (PI) lipid metabolism in mouse uteri and breast cancer cells.…”
Section: Introductionmentioning
confidence: 95%
“…A second messenger pathway is possible if the hormone receptors are associated with membranes or alternatively if the hormone is able to affect directly the membrane-associated signal-transducing enzymes during its passage through the membrane. The presence of specific binding sites for steroid hormones on the membrane of endometrial cells (Pietras & Szego 1977), rat pituitary (Bression et al 1986, Pappas et al 1995 has been demonstrated. Furthermore, Grove & Korach (1987) and Freter et al (1988) have shown enhanced phosphatidyl inositol (PI) lipid metabolism in mouse uteri and breast cancer cells.…”
Section: Introductionmentioning
confidence: 95%
“…Rat gonadotropes express both isoforms of ER, the predominant ERa (Lindzey et al 2006) and ERb at nuclear level (Kuiper et al 1997, Mitchner et al 1998, Vaillant et al 2002, Sánchez-Criado et al 2005a. In addition, an ER which appears to be the same protein as nuclear ERa is expressed at the plasma membrane level (Bression et al 1986, Razandi et al 1999, Toran-Allerand et al 1999, Schmidt et al 2000, Kelly & Levin 2001, Simoncini & Genazzani 2003, Toran-Allerand 2004, Levin 2005. Integration of E 2 effects at different ER pools in the gonadotrope (nuclear ERa and ERb and membrane ERa) determines the cellular actions of E 2 on basal and preovulatory LH secretion and hence on ovulation (Fink 1988(Fink , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the originspecific DNA-binding protein of Bacillus subtilis (13) and the SV-40 large T antigen (14). The only known example of such proteins in eukaryotic cells may be the steroid receptors, which bind DNA to exert their action, and are thought to be associated with the plasma membrane (15)(16)(17). The function ofthe 70-kD protein is not known.…”
Section: Resultsmentioning
confidence: 99%